2004
DOI: 10.1536/jhj.45.397
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Serum Lipoprotein (a) and Residual Lesion Stenosis of Coronary Artery After Myocardial Infarction Without Reperfusion Therapy

Abstract: SUMMARYLipoprotein (a) (Lp(a)) is an independent risk factor for myocardial infarction (MI). It may also inhibit the fibrinolysis system, and Lp (a) affects the natural course of MI and the results of thrombolytic therapy. The purpose of this study was to investigate the influence of Lp (a) on the residual lesion stenosis of the infarction-related arteries (residual stenosis) in acute MI patients in whom reperfusion therapy was not performed.We studied 129 MI patients not given reperfusion therapy who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(18 reference statements)
2
3
0
Order By: Relevance
“…This suggests that Lp(a) may influence intraconary thrombus formation and resolution during MI. This finding is in line with several historical studies coming from thrombolytic era of myocardial infarction treatment, which have shown a higher proportion of spontaneous recanalization of the infarct-related artery in patients with low Lp(a) levels [14][15][16]. However, in another study increased Lp(a) was associated with intermittent occlusion of the infarct-related artery, as compared to the persistent occlusion [17].…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that Lp(a) may influence intraconary thrombus formation and resolution during MI. This finding is in line with several historical studies coming from thrombolytic era of myocardial infarction treatment, which have shown a higher proportion of spontaneous recanalization of the infarct-related artery in patients with low Lp(a) levels [14][15][16]. However, in another study increased Lp(a) was associated with intermittent occlusion of the infarct-related artery, as compared to the persistent occlusion [17].…”
Section: Discussionsupporting
confidence: 89%
“…Notably, typical predictors of fibrinolytic potential were not significant predictors, including levels of plasminogen activator inhibitor type 1 (PAI-1) (108). Similar findings were reported by two other studies in the ensuing years (109,110). However, one very small study (32 subjects) found that Lp(a) levels were higher in MI patients exhibiting intermittent occlusion of the infarct-related artery than patients with persistent occlusion, a result seemingly at odds with an anti-fibrinolytic role for Lp(a) (111).…”
Section: Effect Of Lp(a) On Fibrin Clot Propertiessupporting
confidence: 84%
“…Mechanistic, epidemiological, and recent genetic findings suggest Lp(a) is a causal risk factor for premature atherosclerotic cardiovascular disease (CVD) demonstrating atherogenic and thrombogenic properties, including enhanced uptake by macrophages, interference with fibrinolysis, and increased expression of adhesion molecules [5860]. Lp(a) powerfully inhibits the fibrinolysis system, leading to atherothrombosis and MI [61].…”
Section: Resultsmentioning
confidence: 99%